Dead Exposures: Trophy Bodies and Violent Visibilities of the Nonhuman - Perera, Suvendrini (Borderlands, 2014)
The abject or monstrous body of the killed or tortured nonhuman is evoked throughout Pugliese’s State Violence and the Execution of Law and is critical to the series of carceral and genocidal caesurae that the book so incisively maps. This essay tracks a set of iconological/representational and geopolitical/ideological forces as they intersect the trophy body of the tortured or killed non-human. From Indonesia in 1965 to colonial Kenya and the civil war in SriLanka, the essay considers the violent ramifications of the trophybodies of Abu Ghraib and their symbolic, ideological and affective refractions across other spaces, sites, temporalities and bodies, as well as the counter-visibilities, re-mediations and cultural politics to which they give rise.